Cities of the Mississippi nineteenth-century images of urban development (Univ. of Missouri Press, 1994)
"The mighty Mississippi" has inspired writers and artists for centuries. During the nineteenth century, Mississippi River towns attracted artists who traveled throughout the United States producing detailed drawings of cities and towns, which were then printed and sold as lithographs or used as wood engravings to illustrate books and magazines. Depicting each street and building, as well as the natural setting and geographic features of the surrounding areas, these elaborate bird's-eye views were enormously popular. In Cities of the Mississippi, John W. Reps brings together hundreds of spectacular historical views of Mississippi River towns alongside contemporary aerial photographs and an engaging text. The result is a remarkable voyage through the nineteenth century and a powerful visual record of American urban development. From The Balize, a village for ship pilots near the mouth of the Mississippi, to St. Cloud, Minnesota, at its source, readers will experience Mississippi River towns ranging from the major metropolises of New Orleans, St. Louis, and Minneapolis to the small towns of Cairo, Kaskaskia, and Prairie du Chien. Reps introduces the artists, printers, and publishers who recorded the development of the cities and offers descriptions of the cities by residents, journalists, and travelers in their own words. Spectacular modern aerial photographs of twenty-three of the towns dramatically illustrate changes to the urban scene and demonstrate the lasting influence of the initial city patterns on subsequent growth.